Kedudukan Tanah dan Sumber Hasil menurut Perlembagaan Persekutuan Malaysia (Kanun: Jurnal Undang-undang Malaysia, 2013)
The position of land in the Federal Constitution benchmarks the jurisdiction of the States and the Federal relating to land. The existence of a clear provision for that purpose guarantees States full authority over land and anything becomes part of land, unless provided otherwise. Nevertheless, Parliament can enact laws for the purpose of uniformity of the law. The National Land Code 1965 is one such example. This article examines the extent of State and Federal jurisdictions over land matters and the ensuing challenges. One of the challenges relates to the perception that the power of the State is being encroached. Hence several states have instituted policies that are clearly against the spirit of the decision of the National Land Council as an act of protest. Apart from a keen perusal of the legal provisions, this study has also referred to other secondary data. The findings revealed that even though some States may have land and other resources, the lack of capital and constraints in the law have resulted in less than optimum utilisation of resources. . There is a thus a need to review the policy on finance and law in order to help States improve their economic activities so as to increase their income.Keywords: land, Federal Constitution, National Land Code 1965, water, tax, waqf, State Authority, local authority, National Land Council